Impact assessment of BRAC's human rights and legal education training - Rafi, Mohammad; Hulme, David; Ahmed, Shah Asad; Amin, Md. Nurul (BRAC Research and Evaluation Division (RED), 2019)
The huge training investment of BRAC calls for an answers to the questions -- what is the impact of the training on BRAC programs and on its recipient? This study endeavors to answer these questions. As a part of this effort an impact assessment research methodology for training was developed. The methodology was then applied to the training under Human Rights and Legal Education (HRLE) program. (pp. 1-2) The HRLE training has been introduced to disseminate practically relevant legal knowledge to BRAC members. In order to reach a large number of Village Organization (VO) members at low cost a training 'cascade' has been established. Training is offered al three levels. First comes the Training of Trainers (TOT) for HRLE. Next is Teachers Training (TT) for HRLE Shebok/Shebikas. Finally there is Legal Education (LE) provided by Shebok/Shebikas to the VO members. The laws that the training covers arc Citizen's Right Protection Law, Muslim Family Law, Muslim Inheritence Law, and Land Law. (pp. 3-7)